Comparing effects of starch-based bioplastics and chitosan-starch blends ingestion in supralittoral amphipod Talitrus saltator (Montagu, 1808) - Russo, Alessandro; Pogni, Rebecca; Costa, Jessica; Martellini, Tania; Cincinelli, Alessandra; Cavalieri, Duccio; Ugolini, Alberto (Biologia Marina Mediterranea, 2025)
Abstract - Marine supralittoral environments are particularly endangered by plastic and bioplastic accumulation. In this work, we assessed and compared the effects on survival rate related to ingestion of different kinds of starch-based bioplastics and chitosan-starch mixtures by supralittoral amphipod Talitrus saltator. Groups of adult individuals were fed exclusively with bioplastic/chitosan-starch blends presented as 10x10cm sheets, in controlled conditions. To measure palatability, sheets consumption was calculated using MatLab. Surviving individuals were counted after 14 or 30 days. Results show that chitosan is more palatable by sandhoppers when starch is present at a high percentage in the mixture, while there is no preference for starch-based bioplastics. In addition, after 14 days, survival rate drops drastically around 0% in chitosan experimental groups while, for starch-based bioplastic, survival rate is generally higher even after 30 days, depending on the type of bioplastic. Results highlight a negative effect on survival rate of sandhoppers, particularly regarding chitosan-starch blends.